PENERAPAN METODE PEMBELAJARAN TUTOR SEBAYA PADA PEMBELAJARAN MATEMATIKA MATERI PECAHAN KELAS IV - Novi Dela Anggraini; Apri Irianto; Pana Pramulia (STKIP Bina Bangsa Meulaboh, 2022)
This study aims to explain the activities of student in learning with the application of peer tutoring methods and to describe student responses to the application of peer tutoring methods in class IV-C SD Negeri Kepuh Kiriman I Waru. This research uses qualitative research method with descriptive research type. The data sources for this study is students in grades IV-C with a total of 17 children. Observation and questionnaires were used as data collection methods. This study uses Miles and Huberman qualitative data analysis techniques, namely data reduction, data presentation, and conclusions and verification. The results show the application of Peer Tutor learning methods in grades IV-C could grow and develop student activities, because almost all students were actively involved and very enthusiastic in learning activities, both classical and group activities. Student responses to the learning process with the application of the peer tutor method received a good/positive response from students. With peer tutors, tutee students are more confident to ask questions about material they didn't understand, because the peer tutor’s language was easier to understand.